Novel particulate BCG-loaded delivery system for mucosal immunization against tuberculosis - Caetano, Liliana Aranha (2016)
Tese de doutoramento, Farmácia (Tecnologia Farmacêutica), Universidade de Lisboa, Faculdade de Farmácia, 2016